2010
DOI: 10.1007/s00425-010-1107-z
|View full text |Cite
|
Sign up to set email alerts
|

A functional EDS1 ortholog is differentially regulated in powdery mildew resistant and susceptible grapevines and complements an Arabidopsis eds1 mutant

Abstract: Vitis vinifera (grapevine) is the most economically important deciduous fruit crop, but cultivated grapevine varieties lack adequate innate immunity to a range of devastating diseases. To identify genetic resources for grapevine innate immunity and understand pathogen defense pathways in a woody perennial plant, we focus in this study on orthologs of the central Arabidopsis thaliana defense regulator ENHANCED DISEASE SUSCEPTIBILITY1 (EDS1). The family of EDS1-like genes is expanded in grapevine, and members of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 45 publications
3
33
0
Order By: Relevance
“…Therefore, clustering EDLs in the phylogenic tree showed that EDS1 related proteins of Vitis are novel compared to other plant proteins. These results are consistent with those of a previous report that showed Vitis EDS1 proteins were grouped together in a phylogenetic tree and diverged from other plant proteins (Gao et al 2010). The predicted amino acid sequences from the three loci of the VfEDL gene showed a high level of similarity with protein sequences of other plant species in a homology study of VfEDL genes by BLAST searches of the NCBI database.…”
Section: Amino Acid Sequence Comparisonsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, clustering EDLs in the phylogenic tree showed that EDS1 related proteins of Vitis are novel compared to other plant proteins. These results are consistent with those of a previous report that showed Vitis EDS1 proteins were grouped together in a phylogenetic tree and diverged from other plant proteins (Gao et al 2010). The predicted amino acid sequences from the three loci of the VfEDL gene showed a high level of similarity with protein sequences of other plant species in a homology study of VfEDL genes by BLAST searches of the NCBI database.…”
Section: Amino Acid Sequence Comparisonsupporting
confidence: 92%
“…In the expression study, all three VfEDL genes were upregulated at 1 hpi against bacterial pathogen R. vitis and two genes, VfEDL2 and VfEDL3, also showed upregulation at 1 hpi against fungal pathogen E. ampelina, after which all of them showed reduction in their expressions. This expression pattern was similar to the previous reports about expression pattern of EDS1 genes (Oridi and Bouarab 2007;Gao et al 2010;Wang et al 2014). VfEDL1 showed down regulated expression at all time points against E. ampelina, but its expression was upregulated against R. vitis infection at early time points, suggesting that the VfEDL1 gene functions in diverse response processes against bacterial and fungal pathogens.…”
Section: Expression Analysis Of Vfedl Genessupporting
confidence: 90%
See 1 more Smart Citation
“…Low levels of polymorphism in the two VvNPR genes show that they experienced purifying selection and suggest that they are Complementation of the Arabidopsis npr1 mutation has been performed previously to characterize NPR1 from several crop plants, including rice (Yuan et al 2007), canola (Potlakayala et al 2007), soybean (Sandhu et al 2009), and cacao (Shi et al 2010). Recently, complementation of the Arabidopsis eds1 mutant with grapevine sequences also helped to characterize the function of Vitis EDS1, another central defense regulator acting upstream of SA in pathogen resistance (Gao et al 2010).…”
Section: Discussionmentioning
confidence: 97%
“…EDS1 and PAD4 interact with each other and also function in race-specific resistance derived from multiple R proteins from diverse plants (Parker et al, 1996;Aarts et al, 1998;Feys et al, 2001;Peart et al, 2002;Liu et al, 2002;Hu et al, 2005;Gao et al, 2010). We show that soybean contains two EDS1-like genes and one PAD4-like gene, which encode proteins with significant structural similarities to the Figure 8.…”
Section: Discussionmentioning
confidence: 99%